Preparation method of PANI-ZIF-8 / PA composite coating on surface of metal bipolar plate
By preparing the PANI-ZIF-8/PA composite coating on the stainless steel bipolar plate, the problems of poor adhesion and insufficient long-term immersion performance of the single conductive polymer coating are solved, and the coating effect with high conductivity, corrosion resistance and strong adhesion are achieved, which significantly improves the corrosion resistance of the stainless steel bipolar plate.
Patent Information
- Application Number
- CN202411641578.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-18
AI Technical Summary
In the prior art, the single conductive polymer coating has poor adhesion on stainless steel bipolar plates and insufficient long-term immersion performance, so it cannot effectively prevent corrosion.
Using the preparation method of PANI-ZIF-8/PA composite coating, a composite coating with high conductivity, high corrosion resistance and strong adhesion is formed by spin-coating ZIF-8 material with excellent physical shielding performance on the polyaniline coating substrate.
It significantly improves the corrosion resistance of the conductive polymer coating, enhances the adhesion between the coating and the metal substrate, and extends the long-term immersion performance, effectively preventing corrosion of stainless steel bipolar plates.
Smart Images

Figure CN119592951A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal corrosion protection, and specifically relates to a method for preparing a PANI-ZIF-8 / PA composite coating on the surface of a metal bipolar plate. Background Art
[0002] The fuel (H2 and O2) and product (H2O) involved in the proton exchange membrane fuel cell (PEMFC) are ultra-clean substances, more friendly to the natural environment and pollution-free, and have high power generation efficiency, so it is hailed as one of the most promising power generation devices. PEMFC will degrade SO4 when working. 2- , Cl - and F - Corrosive ions such as ions make the solution weakly acidic, so the bipolar plate material needs to have strong corrosion resistance, and the selection of bipolar plate materials is particularly important. Metals have become popular materials for making stainless steel plates due to their good electrical conductivity, thermal conductivity and mechanical properties. Common metal materials include some precious metals, such as gold and platinum, but they are expensive and not suitable for widespread application. Among metal materials, stainless steel (SS) has become the preferred material due to its good corrosion resistance, easy processing, low cost and high commercial value. However, in the acidic working environment of the bipolar plate, stainless steel faces serious corrosion problems, so certain measures need to be taken to prevent stainless steel corrosion.
[0003] Conductive polymer coatings have good physical shielding properties and anodic protection, and have broad research prospects in the field of metal corrosion protection. However, single conductive polymer coatings have problems such as pore defects, poor adhesion, and insufficient conductivity, which limit their application in the field of bipolar plates.
[0004] In the acidic working environment of PEMFC, polyaniline has better development prospects in the corrosion protection of metal stainless steel plates due to its high conductivity and environmental stability, and is widely used in the surface corrosion protection of materials. DeBerry W found that stainless steel bipolar plates coated with conductive polyaniline coatings can have a good protective effect on the anode; Karpakam V prepared polyaniline / molybdate composite materials with oxalic acid, which have good corrosion resistance, but the pore structure of polyaniline affects its long-term immersion performance. Therefore, the adhesion of a single conductive polymer coating or a simple sustained-release agent-doped composite coating on a stainless steel bipolar plate is poor and the long-term service performance of the coating is insufficient, and it is necessary to improve the existing technology to improve its corrosion resistance. Summary of the invention
[0005] In view of the shortcomings of the prior art such as poor adhesion on stainless steel bipolar plates and poor long-term immersion performance, the present application provides a method for preparing a PANI-ZIF-8 / PA composite coating on the surface of a metal bipolar plate, in which a ZIF-8 material with excellent physical shielding properties is spin-coated on a polyaniline coating to obtain a composite coating with high conductivity, high corrosion resistance and high adhesion, which meets the requirements of proton exchange membrane fuel cells and proton exchange membrane water electrolysis for hydrogen production for metal bipolar plates.
[0006] Technical solution:
[0007] To achieve the above objectives, this application is implemented through the following technical solutions:
[0008] A method for preparing a PANI-ZIF-8 / PA composite coating on a metal bipolar plate surface, the method comprising the following steps:
[0009] Step 1: Grind the metal bipolar plate substrate with sandpaper, ultrasonicate it with ethanol for 10 minutes, and then wash it with deionized water;
[0010] Step 2: Dissolve 3-5 g of 98% sulfuric acid in 100 mL of deionized water according to the mass volume ratio and continue stirring at a stirring speed of
[0011] 500-1000rpm, while adding 2-4g aniline dropwise to obtain aniline prepolymer solution, i.e., polyaniline solution;
[0012] Step 3: using the metal bipolar plate substrate washed with deionized water in step 1 as the working electrode, the platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode, a polyaniline coating is prepared by constant current deposition in the aniline prepolymerization solution prepared in step 2;
[0013] Step 4: Dissolve 5-8 g of zinc nitrate hexahydrate and 5.5-7.5 g of 2-methylimidazole in 100-200 ml of methanol according to the mass volume ratio, stir vigorously at 1500-2000 rpm for 5 min, centrifuge at 8000 rpm for 10 min, repeat the centrifugation process 3-5 times, and dry at 80° C. overnight to obtain ZIF-8 material;
[0014] Step 5: Dissolve 50-100 mg of aqueous acrylate PA in 3-5 ml of deionized water according to the mass volume ratio, ultrasonicate for 10 min, continuously stir the acrylic resin solution at a stirring speed of 800-1000 rpm, and add 100-200 mg of the ZIF-8 material prepared in step 4 to the acrylic resin solution to form a ZIF-8 / PA mixed solution;
[0015] Step 6: Spin-coat the ZIF-8 / PA mixed solution obtained in step 5 onto the surface of the polyaniline coating obtained in step 3 using a gel coater. Spin-coat the entire surface of the sample each time. Repeat the spin-coating process 3-5 times and air-dry for 24 hours to obtain a PANI-ZIF-8 / PA composite coating on the surface of the metal bipolar plate.
[0016] Furthermore, in step 1, the metal bipolar plate substrate is a 304 stainless steel substrate.
[0017] Furthermore, in step 2, the molar ratio of aniline to sulfuric acid is 1:3-3:1.
[0018] Furthermore, the stirring reaction time in step 2 is 1-6h.
[0019] Furthermore, in the step 3, the polarization current in the constant current deposition is 0.1-10 mA / cm 2 , the deposition time is 10-40min.
[0020] Furthermore, in step 4, the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:4-2:1.
[0021] Furthermore, the continuous stirring reaction time in step 5 is 24-36 hours.
[0022] Furthermore, in step 6, the spin coating rate of the coating machine is 1000-4000 rpm, and the spin coating time is 30-120 s.
[0023] Beneficial effects:
[0024] The present application provides a method for preparing a PANI-ZIF-8 / PA composite coating on the surface of a metal bipolar plate, which has the following beneficial effects compared with the prior art:
[0025] 1. This application can effectively solve the problem of pore defects in a single conductive polymer coating by spin coating a ZIF-8 material with excellent physical shielding properties on the original conductive polyaniline coating substrate, thereby greatly improving the anti-corrosion performance of the conductive polymer coating;
[0026] 2. The spin-coated ZIF-8 / PA coating of the present application improves the interface structure between the coating and the metal substrate, prolongs the path for the corrosion ions to penetrate into the coating and contact the metal surface, and improves the adhesion and long-term anti-corrosion performance of the PANI coating on the metal surface;
[0027] 3. The product produced after the partial collapse of the ZIF-8 material introduced in this application under acidic conditions has excellent corrosion inhibition performance. 2-Methylimidazole is both a ligand for synthesizing ZIF-8 and an active corrosion inhibitor. The anti-corrosion performance of the composite coating is improved by superposition of slow release and shielding effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The surface coating changes of pure polyaniline coating and composite coating (PANI-ZIF-8 / 100PA) in the immersion experiment test, where (a) is the pure polyaniline coating before immersion, (b) is the PANI-ZIF-8 / 100PA before immersion, (c) is the pure polyaniline coating after immersion, and (d) is the PANI-ZIF-8 / 100PA after immersion. DETAILED DESCRIPTION
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the specific embodiments of the present invention are described in detail below. Specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific implementation disclosed below.
[0030] Embodiment 1:
[0031] A method for preparing a PANI-ZIF-8 / PA composite coating on a metal bipolar plate surface comprises the following steps:
[0032] Step 1: polish the 304 stainless steel substrate with sandpaper, ultrasonicate it with ethanol for 10 min, and then wash it with deionized water;
[0033] Step 2: Dissolve 4 g of sulfuric acid in 100 mL of deionized water, continue stirring at a stirring speed of 500-1000 rpm, and simultaneously dropwise add 2.79 g of aniline to obtain an aniline prepolymerization solution, i.e., a polyaniline solution;
[0034] Step 3: Using the 304 stainless steel substrate washed with deionized water in step 1 as the working electrode, the platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode, the polyaniline solution prepared in step 2 was subjected to 5 mA constant current deposition for 20 min to prepare a polyaniline coating;
[0035] Step 4: Dissolve 5.95 g zinc nitrate hexahydrate and 6.568 g 2-methylimidazole in 100-200 ml methanol, stir vigorously at 1500-2000 rpm for 5 min, centrifuge at 8000 rpm for 10 min, repeat the centrifugation process 3-5 times, and dry at 80°C overnight to obtain ZIF-8 material;
[0036] Step 5: Dissolve 100 mg of aqueous acrylic resin in 5 mL of deionized water, ultrasonicate for 10 min, stir continuously for 24 h at a stirring speed of 800-1000 rpm, and slowly add 200 mg of the ZIF-8 material prepared in step 4 to the acrylic resin solution to form a ZIF-8 / PA mixed solution;
[0037] Step 6: Spin the ZIF-8 / PA mixed solution prepared in step 5 onto the surface of the polyaniline coating prepared in step 3 at 2000 rpm using a homogenizer for 10 minutes. Spin coat the entire surface of the sample each time, and spin coat 3-5 times. Air dry naturally for 24 hours to obtain a PANI-ZIF-8 / PA composite coating on the surface of the metal bipolar plate, which is used as a conductive anti-corrosion coating on the surface of the metal bipolar plate for proton exchange membrane fuel cells and proton exchange membrane water electrolysis to produce hydrogen.
[0038] Embodiment 2:
[0039] A method for preparing a PANI-ZIF-8 / PA composite coating on a metal bipolar plate surface comprises the following steps:
[0040] Step 1: polish the 304 stainless steel substrate with sandpaper, ultrasonicate it with ethanol for 10 min, and then wash it with deionized water;
[0041] Step 2: Dissolve 4 g of sulfuric acid in 100 mL of deionized water, stir continuously at 500-1000 rpm, and add 2.79 g of aniline dropwise at the same time to prepare an aniline prepolymerization solution, i.e., a polyaniline solution;
[0042] Step 3: using the 304 stainless steel substrate washed with deionized water in step 1 as the working electrode, the platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode, the polyaniline solution prepared in step 2 was subjected to 5 mA constant current deposition for 20 min to prepare a polyaniline coating;
[0043] Step 4: Dissolve 5.95 g zinc nitrate hexahydrate and 6.568 g 2-methylimidazole in 100-200 ml methanol, stir vigorously at 1500-2000 rpm for 5 min, centrifuge at 8000 rpm for 10 min, repeat the centrifugation process 3-5 times, and dry at 80°C overnight to obtain ZIF-8 material;
[0044] Step 5: Dissolve 50 mg of aqueous acrylic acid in 5 mL of deionized water, ultrasonicate for 10 min, and stir continuously for 24 h at a stirring speed of 800-1000 rpm. Slowly add 200 mg of the ZIF-8 material prepared in step 4 to the acrylic resin solution to form a ZIF-8 / PA mixed solution.
[0045] Step 6: Spin the ZIF-8 / PA mixed solution prepared in step 5 onto the surface of the polyaniline coating prepared in step 3 using a sizing machine at 2000 rpm. Spin coat the entire surface of the sample each time for 3-5 times and air dry for 24 hours to obtain a PANI-ZIF-8 / PA composite coating on the surface of the metal bipolar plate.
[0046] Embodiment 3:
[0047] A method for preparing a PANI-ZIF-8 / PA composite coating on a metal bipolar plate surface comprises the following steps:
[0048] Step 1: polish the 304 stainless steel substrate with sandpaper, ultrasonicate it with ethanol for 10 min, and then wash it with deionized water;
[0049] Step 2: Dissolve 4 g of 98% sulfuric acid in 100 mL of deionized water, continue stirring at a stirring speed of 500-1000 rpm, and simultaneously dropwise add 2.79 g of aniline to obtain an aniline prepolymerization solution, i.e., a polyaniline solution;
[0050] Step 3: using the 304 stainless steel substrate washed with deionized water in step 1 as the working electrode, the platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode, the polyaniline solution prepared in step 2 was subjected to 5 mA constant current deposition for 20 min to prepare a polyaniline coating;
[0051] Step 4: Dissolve 5.95 g zinc nitrate hexahydrate and 6.568 g 2-methylimidazole in 100-200 ml methanol, stir vigorously at 1500-2000 rpm for 5 min, centrifuge at 8000 rpm for 10 min, repeat the centrifugation process 3-5 times, and dry at 80°C overnight to obtain ZIF-8 material;
[0052] Step 5: Dissolve 100 mg of aqueous acrylic acid in 5 mL of deionized water, ultrasonicate for 10 min, stir continuously for 24 h at a stirring speed of 800-1000 rpm, and slowly add 100 mg of the ZIF-8 material prepared in step 4 to the acrylic resin solution to form a ZIF-8 / PA mixed solution;
[0053] Step 6: Spin the ZIF-8 / PA mixed solution prepared in step 5 onto the surface of the polyaniline coating prepared in step 3 using a sizing machine at 2000 rpm. Spin coat the entire surface of the sample each time. Repeat the spin coating process 3-5 times and air dry for 24 hours to obtain a PANI-ZIF-8 / PA composite coating on the surface of the metal bipolar plate.
[0054] Embodiment 4:
[0055] A method for preparing a PANI-ZIF-8 / PA composite coating on a metal bipolar plate surface comprises the following steps:
[0056] Step 1: polish the 304 stainless steel substrate with sandpaper, ultrasonicate it with ethanol for 10 min, and then wash it with deionized water;
[0057] Step 2: Dissolve 4 g of 98% sulfuric acid in 100 mL of deionized water, continue stirring at a stirring speed of 800-1000 rpm, and simultaneously dropwise add 2.79 g of aniline to obtain an aniline prepolymerization solution, i.e., a polyaniline solution;
[0058] Step 3: using the 304 stainless steel substrate washed with deionized water in step 1 as the working electrode, the platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode, the polyaniline solution prepared in step 2 was subjected to 5 mA constant current deposition for 20 min to prepare a polyaniline coating;
[0059] Step 4: Dissolve 5.95 g zinc nitrate hexahydrate and 6.568 g 2-methylimidazole in 100-200 ml methanol, stir vigorously at 1500-2000 rpm for 5 min, centrifuge at 8000 rpm for 10 min, repeat the centrifugation process 3-5 times, and dry at 80°C overnight to obtain ZIF-8 material;
[0060] Step 5: Dissolve 50 mg of aqueous acrylic acid in 5 mL of deionized water, ultrasonicate for 10 min, stir the acrylic resin solution for 24 h at a stirring speed of 800-1000 rpm, and slowly add 100 mg of the ZIF-8 material prepared in step 4 to the acrylic resin solution to form a ZIF-8 / PA mixed solution;
[0061] Step 6: Spin the ZIF-8 / PA mixed solution prepared in step 5 onto the surface of the polyaniline coating prepared in step 3 using a sizing machine at 2000 rpm. Spin coat the entire surface of the sample each time. Repeat the spin coating process 3-5 times and air dry for 24 hours to obtain a PANI-ZIF-8 / PA composite coating on the surface of the metal bipolar plate.
[0062] Table 1 Corrosion voltage and corrosion current of four PANI-ZIF-8 / PA composite coatings (PANI-200ZIF-8 / 100PA, PANI-200ZIF-8 / 50PA, PANI-100ZIF-8 / 100PA, PANI-100ZIF-8 / 50PA), pure polyaniline coating and 304SS
[0063]
[0064] From Table 1 and Figure 1 It can be seen that under the protection of polyaniline and PANI-ZIF-8 / PA composite coating, the i corr The coating can significantly reduce the corrosion rate of the bipolar plate by the corrosive medium. The immersion test found that the pure polyaniline coating has poor adhesion on stainless steel and is prone to fall off, while the PANI-ZIF-8 / PA composite coating can still maintain the integrity of the coating after the immersion test, indicating that the long-term service performance is good.
Claims
1. A method for preparing a PANI-ZIF-8 / PA composite coating on a metal bipolar plate surface, characterized in that: The method comprises the following steps: Step 1: Grind the metal bipolar plate substrate with sandpaper, ultrasonicate it with ethanol for 10 minutes, and then wash it with deionized water; Step 2: dissolving 3-5 g of 98% sulfuric acid in 100 mL of deionized water according to a mass-volume ratio, stirring continuously at a stirring speed of 500-1000 rpm, and simultaneously adding 2-4 g of aniline dropwise to obtain an aniline prepolymerization solution, i.e., a polyaniline solution; Step 3: using the metal bipolar plate substrate washed with deionized water in step 1 as the working electrode, the platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode, a polyaniline coating is prepared by constant current deposition in the aniline prepolymerization solution prepared in step 2; Step 4: Dissolve 5-8 g of zinc nitrate hexahydrate and 5.5-7.5 g of 2-methylimidazole in 100-200 ml of methanol according to the mass volume ratio, stir vigorously at 1500-2000 rpm for 5 min, centrifuge at 8000 rpm for 10 min, repeat the centrifugation process 3-5 times, and dry at 80° C. overnight to obtain ZIF-8 material; Step 5: Dissolve 50-100 mg of aqueous acrylate PA in 3-5 ml of deionized water according to the mass volume ratio, ultrasonicate for 10 min, continuously stir the acrylic resin solution at a stirring speed of 800-1000 rpm, and add 100-200 mg of the ZIF-8 material prepared in step 4 to the acrylic resin solution to form a ZIF-8 / PA mixed solution; Step 6: Spin-coat the ZIF-8 / PA mixed solution obtained in step 5 onto the surface of the polyaniline coating obtained in step 3 using a gel coater. Spin-coat the entire surface of the sample each time. Repeat the spin-coating process 3-5 times and air-dry for 24 hours to obtain a PANI-ZIF-8 / PA composite coating on the surface of the metal bipolar plate.
2. The method for preparing the PANI-ZIF-8 / PA composite coating on the surface of the metal bipolar plate according to claim 1, characterized in that: In step 2, the molar ratio of aniline to sulfuric acid is 1:3-3:
1.
3. The method for preparing the PANI-ZIF-8 / PA composite coating on the surface of the metal bipolar plate according to claim 1, characterized in that: The stirring reaction time in step 2 is 1-6h.
4. The method for preparing the PANI-ZIF-8 / PA composite coating on the surface of the metal bipolar plate according to claim 1, characterized in that: The polarization current in the constant current deposition in step 3 is 0.1-10 mA / cm 2 , the deposition time is 10-40min.
5. The method for preparing the PANI-ZIF-8 / PA composite coating on the surface of the metal bipolar plate according to claim 1, characterized in that: In step 4, the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:4-2:1, the mixture is vigorously stirred for 5 minutes, and centrifuged at 8000 rpm.
6. The method for preparing the PANI-ZIF-8 / PA composite coating on the surface of the metal bipolar plate according to claim 1, characterized in that: The stirring reaction time in step 5 is 24-36 hours.
7. The method for preparing the PANI-ZIF-8 / PA composite coating on the surface of the metal bipolar plate according to claim 1, characterized in that: In step 6, the spin coating speed of the coating machine is 1000-4000 rpm, and the spin coating time is 30-120 s.
8. The method for preparing the PANI-ZIF-8 / PA composite coating on the surface of the metal bipolar plate according to claim 1, characterized in that: In step 1, the metal bipolar plate substrate is a 304 stainless steel substrate.
Citation Information
Patent Citations
Polymer composite coating preparation method, bipolar plate and proton exchange membrane fuel cell
CN112201795A
Intelligent metal frame-conductive polymer anticorrosive coating and preparation method and application thereof
CN116145206A
Preparation method of conductive polymer and MXene composite coating on surface of metal bipolar plate
CN116815221A
Bipolar Plate for Fuel Cell and Its Method of Making
KR1020030061484A
Cited By
Preparation method of zinc phthalocyanine doped PANI coating on surface of metal bipolar plate
CN119980387A